Public and private - feminist legal debates edited by Margaret Thornton - E. Cowdery (Law Text Culture, 1997)
Public and Private - Feminist Legal Debates traverses some well-trodden ground as well as exploring new connections between law, feminism and notions of public and private. Edited by Margaret Thornton, it is a collection of essays written by feminist scholars working in the areas of law and legal theory. It evolved out of an initiative by the Research School of Social Sciences at the Australian National University. The School invited feminist legal scholars from other institutions to participate, as visiting speakers, in its Feminism and Law series. The relationship between the public/private distinction, legality and women emerged as a common theme throughout the series and generated the idea for the collection.